The use of cork oak in the ecological and landscape restoration of the Latium Hills - Bellarosa, R; Schirone, B; Busatto, M (SYMPOSIUM ON PLANT BIOTECHNOLOGY AS A TOOL FOR THE EXPLOITATION OF MOUNTAIN LANDS, 1998)
The cork oak (Quercus suber L.) is a western Mediterranean species frequently found in Italy along the Tyrrhenian coast and on the islands. Its economic importance is well known, but the species is also ecologically precious. Notably, in fact, it is extremely resistant to forest fires. Because of its properties a project is on its way to restore the marginal lands of northern Latium through the reforestation with selected specimens of cork oak. The main aims of the project are: the genetic comparison between cork oak of different Italian provenances the establishment of an experimental arboretum which will collect cork oak deriving from the 34 main European areas the running of experimental trials on innovative reforestation techniques, such as the Miyawaki method. The methodology and initial results of the project are reported.
Keywords: arboretum; Cork oak; Genetic variability; reforest

Ribosomal RNA genes inQuercus spp.(Fagaceae) - Bellarosa, R; Delre, V; Schirone, B; Maggini, F (Plant Systematics and …, 1990)
The taxonomy of the genus Quercus is still unclear. In order to elucidate the taxonomy of Mediterranean oaks we have analyzed ribosomal RNA genes of Quercus cerris, Q. coccifera, Q. trojana, Q. ilex, Q. suber, and Q. macrolepis by means of Southern blot hybridization. Oak nuclear DNA was extracted from root tips of 300 acorns and from catkins of single plants. EcoRI and BamHI restriction endonucleases were used. DNA electrophoresis and rRNA/DNA hybridization were performed using Vicia faba rRNA 18 S and 25 S as probes. The rRNA genes of all the species studied have an identical restriction mapping in the 18 S and 25 S regions, while differences in length are present in the intergenic regions. Q. cerris possesses at least four types of genes of 12.1, 11.5, 8.5, and 8.3 kb; Q. coccifera at least three types of 12.4, 10.4, and 10.1 kb; Q. trojana possesses the same rRNA genes as Q. cerris plus another gene type 12.0 kb long, with EcoRI and BamHI restriction sites in the intergenic spacer; Q. ilex at least three types of 12.4, 10.85, and 9.5 kb; Q. suber at least five types of 11.5, 11.0, 8.6, 8.5, and 8.3 kb; Q. macrolepis, finally, at least seven types of 11.5, 11.0, 10.2, 8.6, 8.5, 8.3, and 8.15kb. Q. coccifera and Q. ilex rDNA appears quite different respect to other species examined, while high similarity seems to exist between Q. cerris, Q. trojana, Q. suber, and Q. macrolepis. These results are in agreement with the taxonomic model proposed by SCnWARZ for the genus Quercus.
Keywords: Angiosperms; Fagaceae; Gene mapping; Quercus; ribosomal RNA genes; rRNA/DNA hybridization; taxonomy